2022
DOI: 10.1590/s1982-21702022000300013
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of tropospheric modeling on PPP-AR performances under brazilian atmospheric condition

Abstract: In the Global Navigation Satellite System (GNSS), ambiguity resolution (AR) can shorten observation time and increase the positioning quality. The correct tropospheric modeling is intrinsically related to the ability to perform AR. Here, we assessed the influence of different tropospheric correction alternatives on AR for static Precise Point Positioning (PPP) in Brazilian territory. Our goal was to provide directions to users when choosing a suitable tropospheric model for application in PPP-AR under Brazilia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…PPP-RTK, another advanced GNSS positioning technique, is also confronted by the challenge of processing tropospheric wet delay with high precision. However, the research on integrating NWP ZWD information with GNSS technology is not extensive (Theodoro et al 2022), and no studies have reported the performance of NWP ZWD-augmented PPP-RTK.…”
Section: Introductionmentioning
confidence: 99%
“…PPP-RTK, another advanced GNSS positioning technique, is also confronted by the challenge of processing tropospheric wet delay with high precision. However, the research on integrating NWP ZWD information with GNSS technology is not extensive (Theodoro et al 2022), and no studies have reported the performance of NWP ZWD-augmented PPP-RTK.…”
Section: Introductionmentioning
confidence: 99%